A Novel Ce─Mn Heterojunction‐Based Multi‐Enzymatic Nanozyme with Cancer‐Specific Enzymatic Activity and Photothermal Capacity for Efficient Tumor Combination Therapy - Qiao, Qianqian; Liu, Zerui; Hu, Fei; Xu, Ziqiang; Kuang, Ying; Li, Cao (Advanced functional materials, 2025)
Catalytic medicine, using enzymes or nanozymes, is an emerging method for cancer treatment. However, its applicability is limited by the low catalytic activity in the tumor microenvironment (TME). In this work, a versatile and synthesis‐friendly nanozyme, CeO2Mn1.08Ox nanoclusters, is prepared. This novel Ce─Mn heterojunction is formed by oxidation of CeO2 nanoparticles through H2SO4/KMnO4. CeO2Mn1.08Ox exhibits high multi‐enzymatic catalytic activities and acts as a catalase (CAT), peroxidase (POD), and oxidase (OXD) mimics under acidic conditions. It can regulate the TME by relieving hypoxia and consuming endogenous glutathione (GSH). Glucose oxidase (GOx) is then incorporated into CeO2Mn1.08Ox and linked with poly(ethylene glycol) (PEG) to obtain the cascade enzyme system (Ce─Mn)‐PEI/GOx‐PEG. CeO2Mn1.08Ox exhibits CAT‐like properties, which sensitize GOx‐based starvation therapy, and POD‐ and OXD‐like properties, which generate highly cytotoxic reactive oxygen species (ROS) in cancer cells. The glucose catabolic product, H2O2, is also used to generate O2 and ROS. In addition, the heterojunction structure provides CeO2Mn1.08Ox with near‐infrared (NIR) photothermal capability, making it suitable for photothermal therapy (PTT). Density functional theory (DFT) calculations provide possible reasons for the high catalytic activity and photothermal capability of CeO2Mn1.08Ox. When combining mild PTT with catalytic therapy, the cascade enzyme system (Ce─Mn)‐PEI/GOx‐PEG can efficiently ablate tumors. The novel Ce─Mn heterojunctions, CeO2Mn1.08Ox nanoclusters, are reported and are used to construct the cascade enzyme system (Ce─Mn)‐PEI/GOx‐PEG. The heterojunction structure provides CeO2Mn1.08Ox with good multi‐enzyme activities and photothermal ability. (Ce─Mn)‐PEI/GOx‐PEG enables efficient catalysis of enzymatic cascade reactions in cancer cells, glucose consumption, and ROS generation, and can be coupled with mild PTT for efficient tumor inhibition.